The century of science : the global triumph of the research university - Powell, Justin J. W.; Baker, David P.; Fernandez, Frank, active 2017 (Emerald Publishing Limited, 2017)
In The Century of Science, a multicultural, international team of authors examine the global rise of scholarly research in science, technology, engineering, mathematics, and health (STEM+) fields. This insightful text provides historical and sociological understandings of the ways that higher education has become an institution that, more than ever before, shapes science and society. Case studies, supported by the most historically and spatially extensive database on STEM+ publications available, of selected countries in Europe, North America, East Asia, and the Middle East, emphasize recurring themes: the institutionalization and differentiation of higher education systems to the proliferation of university-based scientific research fostered by research policies that support continued university expansion leading to the knowledge society. Growing worldwide, research universities appear to be the most legitimate sites for knowledge production. The chapters offer new insights into how countries develop the university-based knowledge thought fundamental to meeting social needs and economic demands. Despite repeated warnings that universities would lose in relevance to other organizational forms in the production of knowledge, these findings demonstrate incontrovertibly that universities have become more - not less - important actors in the world of knowledge. The past hundred years have seen the worldwide triumph of the research university.
Prelims -- Introduction: the worldwide triumph of the research university and globalizing science -- Higher education expansion and the growth of science: the institutionalization of higher education systems in seven countries, 1945 - 2015 -- The European Center of Science Productivity: Research universities and institutes in France, Germany, and the United Kingdom -- Science production in the United States: An unexpected synergy between mass higher education and the super research university -- Changing science production in Japan: The expansion of competitive funds, reduction of block grants, and unsung heroes -- The rise of higher education and science in China -- Science production in Taiwanese Universities, 1980 - 2011 -- The growth of higher education and science production in South Korea since 1945 -- Fever of research: scientific journal article production and the emergence of a national research system in Qatar, 1980 - 2011 -- STEM+ PRoductivity, development, and wealth, 1900 - 2012 -- About the Authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Universities and colleges -- Sociological aspects; Research -- History; Education, Higher